Botulinum toxin for the treatment of hypercontractile esophagus: Results of a double‐blind randomized sham‐controlled study. Issue 5 (11th April 2019) - Mion, François; Marjoux, Sophie; Subtil, Fabien; Pioche, Mathieu; Rivory, Jerome; Roman, Sabine; Zerbib, Frank
Abstract: Introduction: Botulinum toxin injection is known to be efficient to treat achalasia. We conducted a randomized trial in order to evaluate its efficacy to treat symptomatic hypercontractile esophageal disorders as characterized by esophageal high‐resolution manometry. Methods: Patients with significant dysphagia and/or thoracic pain related to an hypercontractile esophageal motility disorder as defined by the Chicago Classification were randomized to receive an injection of botulinum toxin (100 U in 10 points in the distal part of the esophageal wall) or a sham procedure. Symptoms were assessed at 3 months with the Eckardt score. Patients could receive a first or second botulinum toxin injection 1 month later if symptoms persisted. Results: Twenty‐three patients (13 women, mean age 60 years) were included: 13 received botulinum toxin injection, and 10 a sham procedure. The improvement of symptoms at 3 months was significant compared to baseline, but similar in the active treatment and sham procedure arms. However, there was no change in quality of life scores. Seventeen patients received a second injection at 4 months. There was a significant trend toward improvement of symptoms up to the end of follow‐up at 12 months, without a significant relationship with the administration of botulinum toxin. Discussion: Botulinum toxin injection is not superior to a sham procedure to improve symptoms related to hypercontractile esophageal disorders, suggesting an important placebo effect in for this type of disease. This observation must be taken into account when evaluating more aggressive therapies such as endoscopic myotomy (clinicaltrials.gov: NCT01955174). Abstract : Twenty‐three patients with hypercontractile esophagus were randomized to esophageal botulinum toxin injection or sham procedure. There was a significant improvement of the symptoms at 3 months, similar in both arms. Clinical symptoms of hypercontractile esophagus may improve spontaneously over time.